Fatal Intoxication by the Novel Cathinone 4-Fluoro-3-methyl-α-PVP. Issue 3 (11th January 2022) - Hobbs, Jennifer M; DeRienz, Rebecca T; Baker, Daniel D; Shuttleworth, Morgan R; Pandey, Maneesha
Abstract: A 30 year old non-hispanic white male was found unresponsive at his workplace and admitted to the hospital in cardiac arrest. He was pronounced deceased shortly after arrival. At autopsy the pathologist noted a 176 pound, well-nourished, atraumatic, adult male with significant bilateral frothy pulmonary edema (right lung 930 g and left lung 1, 130 g), cardiomegaly (430 g), dilated ventricles and slight cerebral edema. Upon completion of the systematic toxicological analysis scope for the Franklin County Coroner's Office Toxicology Laboratory, no known drugs were found. Further review of the gas chromatography--mass spectrometry (GC--MS) full-scan library summary reports showed an unknown peak in both the blood and urine solid phase extracts. An analogue of α-pyrrolidinovalerophenone (α-PVP) was identified, and a GC--MS selected ion monitoring method was developed to identify and quantitate the presence of 4-fluoro-3-methyl-α-PVP. This method quantified the drug at 26 ng/mL in gray top femoral blood, 30 ng/mL in purple top heart blood and 20 ng/mL in red top vitreous humor. Qualitative presence was also observed in the urine but was not detected in the liver. The decedent's cause of death was determined to be due to fluoro-methyl-PVP toxicity and the manner was ruled to be accidental. Investigational follow-up interviews corroborated drug use by the deceased with a preference of research chemicals and synthetic cannabinoids via the internet. No published literature is available currently, and to the author's knowledge this is the first incident of a fatal death solely attributed to this substituted cathinone.